The life and adventures of Henry Bibb : an American slave - Bibb, Henry, 1815-1854 (Wisconsin studies in autobiography., 2001)
First published in 1849 and largely unavailable for many years, The Life and Adventures of Henry Bibb is among the most remarkable slave narratives. Born on a Kentucky plantation in 1815, Bibb first attempted to escape from bondage at the age of ten. He was recaptured and escaped several more times before he eventually settled in Detroit, Michigan, and joined the antislavery movement as a lecturer. Bibb's story is different in many ways from the widely read Narrative of the Life of Frederick Douglass, An American Slave and Harriet Jacobs' Incidents in the Life of a Slave Girl . He was owned by a Native American; he is one of the few ex-slave autobiographers who had labored in the Deep South (Louisiana); and he writes about folkways of the slaves, especially how he used conjure to avoid punishment and to win the hearts of women. Most significant, he is unique in exploring the importance of marriage and family to him, recounting his several trips to free his wife and child. This new edition includes an introduction by literary scholar Charles Heglar and a selection of letters and editorials by Bibb.